Develop your leadership skills - Adair, John Eric, 1934- (Creating success ;, 2013)
Suitable for anyone who wishes to improve or develop their leadership skills, this book offers stimulating insights into recognizing and developing individual leadership qualities, acquiring personal authority and, most importantly, mastering core leadership functions such as planning, communicating and motivating.